Feasibility of quick response-based quality improvement projects in an urban primary care setting: A cross-sectional survey - Zi-Yi Yeoh; Hooi Chin Beh; Megat Mohamad Amirul Amzar Megat Hashim; Haireen Abdul Hadi; Deik Roy Chuan; Sajaratulnisah Othman (Malaysian Family Physician)
Introduction: Using quick response (QR) codes to disseminate information has become increasingly popular since the declaration of COVID-19 as a pandemic. We aimed to investigate the feasibility of implementing QR-based quality improvement projects in our clinic to improve patients’ medical knowledge, experience and access to care. Methods: We utilised systematic random sampling by recruiting every 25th patient registered in our clinic during data collection. Participants answered a self-administered printed questionnaire regarding their smartphone usage and familiarity with QR code scanning at the patients’ waiting area. Data were analysed using the Statistical Package for the Social Sciences version 26. Results: A total of 323 patients participated (response rate=100%). The participants’ median age was 57 years (interquartile range=41–67). Most participants were women (63.1%). Approximately 90.4% (n=282) used smartphones, with 83.7% (n=261) reporting average or good usage proficiency. More than half (58.0%) accessed medical information via their smartphones, and 67.0% were familiar with QR codes. Multiple logistic regression analyses revealed that familiarity with QR codes was linked to age of <65 years [adjusted odds ratio (AOR)=4.593, 95% confidence interval (CI)=2.351–8.976, P<0.001], tertiary education (AOR=2.385, 95% CI=1.170–4.863, P=0.017), smartphone proficiency (AOR=4.703, 95% CI=1.624–13.623, P=0.004) and prior smartphone usage to access medical information (AOR=5.472, 95% CI=2.790–10.732, P<0.001). Conclusion: Since smartphones were accessible to most primary care patients, and more than half of the patients were familiar with QR code scanning, QR code-based quality improvement projects can be used to improve services in our setting.